The impact of school closures on learners’ mental health in the context of COVID-19 in the City of Cape Town - Chauke, Thulani Andrew; Obadire, Olusegun Samson (Research in Social Sciences and Technology, 2024)
This paper explores the negative impact of the shutdown of contact-based learning on learners’ mental health as a result of COVID-19 and provides recommendations to promote learners’ mental health during and post COVID-19. A qualitative research method was used to guide the collection and analysis of the data. Data was collected from a sample of 20 learners from Cape Town and analysed through thematic analysis. The study findings revealed that with the shutdown of contact-based learning as one of the COVID-19 containment measures by the government learners experienced social anxiety disorder and sleeping disorder. Youth policymakers need to design interventions that promote mental health in after-school programmes implemented by qualified youth workers and social workers. Youth workers should take the courses of action in a non-formal education to promote youth mental health.